A methodological approach for simulating musculoskeletal loading in the head and neck region following boxing punches to the head - Paldauf, S.; Potthast, W.; Kommik, I. (ISBS Proceedings Archive (Michigan), 2022)
The aim of various combat sports is to win the competition by throwing repetitive punches predominantly to the opponent's head. These hitting blows can lead to short and potentially long-term adverse health consequences. The aim of the current study is to introduce an approach that estimates 3D punch forces acting on a struck subject's head. The procedure refers to marker-based kinematic measures and subsequently implementing them into a musculoskeletal head-neck model in OpenSim. The results showed reasonable effective mass estimates, whereby the relatively small force magnitudes and the activation of the reserve moments require methodological modifications followed by the validation of the proposed approach.